Optimalisasi pengelolaan keuangan mahasiswa melalui pencatatan keuangan berbasis financial technology - Nur Rahmawati, Zahra (Maliki Interdisciplinary Journal, 2025)
Financial management is an important skill for students to maintain stability and anticipate various financial problems in the future. However, many students still face difficulties in recording and managing their finances regularly. The development of financial technology (fintech) offers solutions by providing features for automatic transaction recording, expenditure analysis, budget preparation, and digital financial literacy education. This conceptual article aims to analyze how fintech can function in optimizing student financial recording. The discussion covers the importance of financial management, the benefits of financial recording, the role of fintech, the challenges of its use, and optimization efforts that can be made. The results of the analysis show that fintech can improve the efficiency and accuracy of student financial recording, but its use is still hampered by low digital financial literacy, data security risks, consumptive behavior, and limited access to technology. Therefore, optimizing fintech-based financial record-keeping requires improving financial literacy, selecting safe and reliable applications, conducting regular evaluations, and securing support from educational institutions. Thus, fintech has the potential to become a strategic tool in helping students achieve financial independence.